Task matters - challenging the motor system allows distinguishing unaffected Parkin mutation carriers from mutation-free controls. (May 2021) - Prasuhn, Jannik; Borsche, Max; Hicks, Andrew A.; Gögele, Martin; Egger, Clemens; Kritzinger, Cleo; Pichler, Irene; Castelo-Rueda, Maria Paulina; Langlott, Lynn; Kasten, Meike; Mascalzoni, Deborah; Klein, Christine; et al.
Abstract: Background: Heterozygous carriers of Parkin mutations are suggested to be at risk of developing Parkinson's disease, while biallelic variants are associated with typical autosomal recessive early-onset PD. Investigating unaffected heterozygous mutation carriers holds the potential of a deeper understanding of monogenic PD and has implications for PD in general, in particular regarding the prodromal phase. Objectives: To discriminate healthy Parkin mutation carriers from healthy non-mutation carriers using a multimodal approach. Methods: Twenty-seven healthy heterozygous Parkin mutation carriers (13 female. age: 48 ± 13 years) and 24 healthy non-mutation carriers (14 female. age: 48 ± 15 years) from the CHRIS study (Cooperative Health Research in South Tyrol) were recalled based on their genetic profile and underwent a blinded assessment of motor and non-motor PD symptoms, transcranial sonography and sensor-based posturography and gait analyses under different conditions with increasing difficulty. For the latter, gradient-boosted trees were used to discriminate between carriers and non-carriers. The classification accuracy and the area under the curve of the receiver-operator characteristics curve were calculated. Results: We observed no differences concerning motor or non-motor symptoms and substantia nigra hyperechogenicity. The best gradient-boosted trees-based model on posturography measurements (tandem feet, eyes closed, firm surface), however, showed a classification accuracy of up to 86%. The best-performing gradient-boosted trees-based model for gait analyses showed a balanced accuracy of up to 87% (dual-tasking). Conclusions: Sensor-based quantification of movements allows to discriminate unaffected heterozygous mutation carriers from mutation-free controls. Thereby, it is crucial to challenge the motor system with more difficult tasks to unmask subtle motor alterations. Highlights: Subtle motor alterations can be detected in healthy Parkin mutation carriers. Only higher demands on motor task performance are discriminatory. We detected subtle motor alterations before significant motor symptoms. Motor alterations are already present in the absence of other prodromal markers.